Clinicopathologic characterization of cervical metastasis from an unknown primary tumor: a multicenter study in Korea - Miseon Lee; Uiree Jo; Joon Seon Song; Youn Soo Lee; Chang Gok Woo; Dong-Hoon Kim; Jung Yeon Kim; Sun Och Yoon; Kyung-Ja Cho (Korean Society of Pathologists & the Korean Society for Cytopathology, 2023)
Background Research regarding cervical metastasis from an unknown primary tumor (CUP) according to human papillomavirus (HPV) and Epstein-Barr virus (EBV) status in Korea has been sporadic and small-scale. This study aims to analyze and understand the characteristics of CUP in Korea according to viral and p16 and p53 status through a multicenter study. Methods Ninety-five cases of CUP retrieved from six hospitals in Korea between January 2006 and December 2016 were subjected to high-risk HPV detection (DNA in situ hybridization [ISH] or real-time polymerase chain reaction), EBV detection (ISH), and immunohistochemistry for p16 and p53. Results CUP was HPV-related in 37 cases (38.9%), EBV-related in five cases (5.3%), and unrelated to HPV or EBV in 46 cases (48.4%). HPV-related CUP cases had the best overall survival (OS) (p = .004). According to the multivariate analysis, virus-unrelated disease (p = .023) and longer smoking duration (p < .005) were prognostic factors for poor OS. Cystic change (p = .016) and basaloid pattern (p < .001) were more frequent in HPV-related cases, and lymphoepithelial lesion was frequent in EBV-related cases (p = .010). There was no significant association between viral status and p53 positivity (p = .341), smoking status (p = .728), or smoking duration (p = .187). Korean data differ from Western data in the absence of an association among HPV, p53 positivity, and smoking history. Conclusions Virus-unrelated CUP in Korea had the highest frequency among all CUP cases. HPV-related CUP is similar to HPV-mediated oropharyngeal cancer and EBVrelated CUP is similar to nasopharyngeal cancer in terms of characteristics, respectively.